Leadership and Mentoring - Huff, Brenda (Operating Room Nurses Association of Canada Journal, 2004)
In today’s working environment a leader has to demonstrate qualities of honesty, integrity, loyalty, trustworthiness, principled behaviour and understanding ).1 Leadership begins with practicing personal accountability; identifying how you can make a difference; and never under-estimating the power of one person to make a difference. A means to do this is by being a mentor and being mentored.